Modelling adsorption in fluorinated TKL MOFs. Issue 3 (11th February 2017) - Ray, Promit; Bonakala, Satyanarayana; Balasubramanian, Sundaram
Abstract: Ligand functionalisation resulting in unprecedented enhanced adsorption in a series of structurally similar, fluorinated metal-organic frameworks is studied using molecular computations and simulations. Strikingly anomalous experimental trends in the adsorption characteristics of the TKL FMOFs are investigated and understood here using classical and quantum chemical methods. Almost identical adsorption sites and energies for all the MOFs considered herein were observed. However, experimental isosteric heats and uptake amounts between these solids have been reported to be significantly different. Therefore, ab initio molecular dynamics simulations are performed to account for the drastic effects that flexible linkers can have on gas adsorption energetics, something that low-temperature crystallographic measurements cannot completely capture.